2007
DOI: 10.1007/s00423-007-0164-7
|View full text |Cite
|
Sign up to set email alerts
|

Depressed T cell-derived IFN-γ following trauma-hemorrhage: a potential mechanism for diminished APC responses

Abstract: Prolonged immunosuppression after trauma-hemorrhage appears to be predominantly due to diminished T cell function. Thus, attempts to prevent immunodysfunction should be directed towards T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
2
22
0
1
Order By: Relevance
“…[10][11][12] Defective immune responses have been shown for both T-cells and APCs following trauma and severe blood loss. In this regard, T-cells exhibit reduced capacities to proliferate and to release cytokines such as IL-2 and IFN-g. 2,13 Similar to T-cells, APCs function is also suppressed following trauma-hemorrhage, as indicated by decreased cytokine releases and reduced antigen presentation via diminished MHC II expression. 2,4 In those studies, however, T-cells and APCs were not separated prior …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[10][11][12] Defective immune responses have been shown for both T-cells and APCs following trauma and severe blood loss. In this regard, T-cells exhibit reduced capacities to proliferate and to release cytokines such as IL-2 and IFN-g. 2,13 Similar to T-cells, APCs function is also suppressed following trauma-hemorrhage, as indicated by decreased cytokine releases and reduced antigen presentation via diminished MHC II expression. 2,4 In those studies, however, T-cells and APCs were not separated prior …”
Section: Discussionmentioning
confidence: 99%
“…15 Similarly, recent studies by our group using a co-culture system following immune cell separation demonstrated that trauma-hemorrhaged T-cells are able to depress IL-12 release by APCs. 2 However, the release of the T-cell cytokine IFN-g remained unaffected by trauma-hemorrhaged APCs. These results suggested that dysfunctional T-cells might be primarily responsible for the persistent immunosuppression observed following trauma-hemorrhage.…”
Section: T -H a P C T -H T C T -H A P C T -H T C S H A Mmentioning
confidence: 99%
See 3 more Smart Citations